Based on Environmental Local Knowledge the Community rejects Government Project in Solok Sumatra, Indonesia - Syafnil Syafnil; Maskota Delfi; Yevita Nurti (Sosial Horizon: Jurnal Pendidikan Sosial, 2023)
To fulfill on the national energy policy, various countries have initiate the construction of non-fossil fuel geothermal power plants. In Indonesia, it is carried out by one of thone planned at mount Talang in West Sumatera. The government believes this plan will provide equitable benefit for the community.  Nevertheless the current program has brought resistance from the community as considers to have a negatif impact on their future livinghood. It appears to give priority to the government’s national perspective of the project, without talking in consideration the long standing local experience and knowledge of the geothermal environment and its potential hazard. The government has discounted the long term negative effect of the exploration of the environment as put forward by local community. It seen the community’s raised local knowledge on hazardous effect has been left out at this planning stage. The results of this studies shows the current environment is an integerated part of a sustainable harvest regime of the communities around Mount Talang. Its relationship in based on the accumulation of locally collected knowledge and activities. Natural resource utility, community habits and customary taboo have assited in this sustainable harvesting. The planned current utility of geothermal forces has opted the communities to reject curren development plants in its current presentation